Analytic inversion in synthetic aperture radar. - Rothaus, O S (1994)
A method of processing synthetic aperture radar signals that avoids some of the approximations currently in use that appear to be responsible for severe phase distortions is described. As a practical matter, this method requires N3 numerical operations, as opposed to the N2 ln N currently the case, but N3 is now easily managed, for N in the range of interest.